2015
DOI: 10.1002/cne.23866
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and epigenetic mechanisms of early cortical development: An examination of how Pax6 coordinates cortical development

Abstract: The development of the cortex is an elaborate process which integrates a plethora of finely tuned molecular processes ranging from carefully regulated gradients of transcription factors, dynamic changes in the chromatin landscape or formation of protein complexes to elicit and regulate transcription. Combined with cellular processes such as cell type specification, proliferation, differentiation and migration, all of these developmental processes result in the establishment of an adult mammalian cortex with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 176 publications
0
51
0
Order By: Relevance
“…Another neuron subtype identified in our study is the Pax6 + GABAergic neuron (GABA6). Pax6 has an established function in neural development (Ypsilanti and Rubenstein, 2016), but its expression profile and function in the adult brain is largely unknown. A recent study has identified a Pax6 + interneuron population in layer I of cerebral cortex (Zeisel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Another neuron subtype identified in our study is the Pax6 + GABAergic neuron (GABA6). Pax6 has an established function in neural development (Ypsilanti and Rubenstein, 2016), but its expression profile and function in the adult brain is largely unknown. A recent study has identified a Pax6 + interneuron population in layer I of cerebral cortex (Zeisel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…PAX6 is crucial for the generation of neuronal lineages in the CNS including the cortex and retina, as well as the differentiation of non-neuronal lineages of the eye (17)(18)(19). This TF acts in these situations as both a transcriptional activator and repressor via complex gene regulatory networks that are only partly resolved (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Pax6 is a highly conserved transcriptional factor among vertebrates and is crucial for brain development by regulating expression of many downstream genes in highly context-dependent manners [17–22]. It has been recently reported that Pax6 interacts with chromatin remodeling complexes such as BAF and CTCF [2325].…”
Section: Introductionmentioning
confidence: 99%